Strategi Learning Organization Berbasis Model SECILO Dalam Meningkatkan Kinerja Kelembagaan Pendidikan Islam - Titi Hendrawati; Sohwatun Hanifah (PT. Pusmedia Group Indonesia, 2026)
This study aims to analyze the implementation of the SECILO Model as a learning organization strategy to enhance the organizational performance of Islamic educational institutions. Knowledge management has become a strategic necessity for Islamic educational institutions to respond to organizational change, foster innovation, and improve institutional governance. This study employed a qualitative approach using a literature review method by systematically analyzing relevant scholarly articles, books, and academic documents related to the SECILO Model, learning organizations, and Islamic education management. The findings indicate that the implementation of the four SECILO stages socialization, externalization, combination, and internalization strengthens knowledge-sharing practices, improves decision-making effectiveness, promotes organizational innovation, and enhances institutional performance. The effectiveness of the model is influenced by visionary leadership, a collaborative organizational culture, human resource competencies, and the utilization of information technology. This study concludes that the SECILO Model provides a relevant conceptual framework for developing adaptive, innovative, and sustainable learning organizations within the context of Islamic Education Management.